2006
DOI: 10.3892/or.15.4.983
|View full text |Cite
|
Sign up to set email alerts
|

Operational criteria for selecting a cDNA microarray data normalization algorithm

Abstract: Abstract. Microarray technology allows gene expression profiling at a global level. Many algorithms for the normalization of raw microarray data have been proposed, but no attempt has yet been made to propose operationally verifiable criteria for their comparative evaluation, which is necessary for the selection of the most appropriate method for a given dataset. This study develops a set of operational criteria for assessing the impact of various normalization algorithms in terms of accuracy (bias), precision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The calculation of the bias and variance of the expression values for these probes, which is described in detail in Materials and methods (equations [1], [2], [5] and [6]), appears to be the most obvious measure to differentiate among normalization methods. Following the procedure described in the study by Argyropoulos et al (67), we also assumed that the normalization method that gives the lowest bias and variance values for the control spots should be selected as the most appropriate method. Using equations [1] and [2] for double-channel normalization and equations [5] and [6] for single-channel normalization, we calculated the bias and variance values for the control probes present in each of the four datasets.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The calculation of the bias and variance of the expression values for these probes, which is described in detail in Materials and methods (equations [1], [2], [5] and [6]), appears to be the most obvious measure to differentiate among normalization methods. Following the procedure described in the study by Argyropoulos et al (67), we also assumed that the normalization method that gives the lowest bias and variance values for the control spots should be selected as the most appropriate method. Using equations [1] and [2] for double-channel normalization and equations [5] and [6] for single-channel normalization, we calculated the bias and variance values for the control probes present in each of the four datasets.…”
Section: Resultsmentioning
confidence: 99%
“…However, the use of graphical tools is intuitive and often based on the subjective perception of the researcher. In our opinion, a much more elegant and objective solution was proposed in the study by Argyropoulos et al (67), who indicated that the most important aspects of the selection of a normalization algorithm are accuracy, precision and over-fitting. These three aspects can be verified using the bias, variance and relative entropy, respectively, which can be calculated by mathematical formulae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The values of the factors were estimated in the development subset and were used to correct the validation subset. We used empirical measures of variance (58,59) for the assessment of the effects of bias correction using the methods proposed in this paper. The Root Mean Square Error (RMSE), i.e.…”
Section: Methodsmentioning
confidence: 99%